2020
DOI: 10.1093/arclin/acaa048
|View full text |Cite
|
Sign up to set email alerts
|

Self-Awareness Moderates the Association Between Executive Dysfunction and Functional Independence After Acquired Brain Injury

Abstract: Objective Impaired self-awareness (SA) is a common symptom after suffering acquired brain injury (ABI) which interferes with patient’s rehabilitation and their functional independence. SA is associated with executive function and declarative memory, two cognitive functions that are related to participants’ daily living functionality. Through this observational study, we aim to explore whether SA may play a moderator role in the relation between these two cognitive processes and functional ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
0
13
0
2
Order By: Relevance
“…Treatment of impaired self-awareness has been associated with a broad range of outcomes, such as depressive symptoms, functional independence and enhanced activity and participation (Engel et al, 2019;Smeets et al, 2017;Villalobos et al, 2020). In addition, goal setting, especially individually made treatment goals, can improve therapy adherence (Brett et al, 2017;Knutti et al, 2020).…”
Section: Discussion and Applications For Treatment Relevant To Offendersmentioning
confidence: 99%
“…Treatment of impaired self-awareness has been associated with a broad range of outcomes, such as depressive symptoms, functional independence and enhanced activity and participation (Engel et al, 2019;Smeets et al, 2017;Villalobos et al, 2020). In addition, goal setting, especially individually made treatment goals, can improve therapy adherence (Brett et al, 2017;Knutti et al, 2020).…”
Section: Discussion and Applications For Treatment Relevant To Offendersmentioning
confidence: 99%
“…While our findings mirror the general neurological and cognitive heterogeneity of TBI [ 37 , 38 ], they demonstrate that some patients with TBI can benefit from introspection to improve their memory performances. TBI are heterogeneous in nature, and patients with TBI have significant variations in the location and severity of injury, resulting in a significant variation in cognitive performances and insight [ 33 , 48 , 49 , 50 ]. This cognitive variation may explain why some patients with TBI may benefit from introspection to improve destination memory while others fail to do so.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, previous studies have also identified lower use of cognitive strategies such as self-checking and pausing and re-reading during WCPA completion as important indicators of self-monitoring deficits in stroke patients (Jaywant et al, 2022 ) and in an older patients population (Arora et al, 2021 ). Additionally, several studies (Villalobos et al, 2020 ; Fogel, 2022 ) have considered the use of strategies and metacognition (i.e. self-awareness) as factors capable of modulating the typical relationship between ADL and EF.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from neuropsychological and occupational studies has shown that the impairment of these processes is one of the leading causes of functional alterations, keeping individuals from independently returning to their home, community, and job (Kennedy et al, 2008 ), significantly affecting their employment status (Atchison et al, 2004 ; Ownsworth and Shum, 2009 ), and making them incapable of living independently at home (Lipskaya-Velikovsky et al, 2018 ; Ghaffari et al, 2021 ) and engaging in social relationships (Reid-Arndt et al, 2007 ). Furthermore, EF has shown to be a strong predictor of the level of dependency in instrumental activities of daily living (IADL) (Overdorp et al, 2016 ; Villalobos et al, 2020 ), and it can explain a larger percentage of variance in IADL than other cognitive processes (Royall et al, 2007 ; McAlister and Schmitter-Edgecombe, 2016 ). For these reasons, recognizing executive dysfunction and its consequences in everyday activities should be considered when assessing cognitive functions.…”
Section: Introductionmentioning
confidence: 99%